On the relationship between caring and coaching leadership - Kuusilehto-Awale, Lea (Vodenje v vzgoji in izobraževanju, 2014)
This first attempt to map the territory between caring and coaching leadership posits that they share a common basis. A human-centred leadership philosophy of the educational leader and the sports coach is vital to the relationship between the educator/educatee and the coach/coachee, and leads to a socio-constructivist and experiential concept of knowledge and learning, where leading learning consciously takes place through interaction and sharing. Caring and coaching leadership are realized in a relational interaction based on mutual consent and trust which generate self-confidence, respect and commitment, a circumstance for learning and working devoid of intimidation, humiliation and oppression.
Keywords: caring; coaching; filozofija vodenja; human-centred philosophy; leadership; profesionalni razvoj; ravnatelji; relationality; strokovna usposobljenost; trenerji; vodenje